Optimization and field application of an eco-friendly molasses-based dust suppressant for open-pit coal mine haul roads - Yu Zhang; Junlong Yan; Wei Zhou; Weiqing Zhang; Xiang Lu; Peiyuan Li; Fanghui Yang; Zhifan Wang (Scientific Reports)
Abstract To overcome the limitations of conventional water-based dust suppression in arid, high-temperature open-pit coal mine haul roads, this study developed an innovative molasses-based dust suppressant with enhanced water retention and consolidation capabilities. The formulation leverages molasses-a sugar industry byproduct with inherent anti-evaporation properties-as its core component, supplemented with surfactant (sodium dodecyl benzene sulfonate, SDBS), humectant (glycerol), and hygroscopic (calcium chloride, CaCl₂) additives. Employing response surface methodology (RSM), the optimal composition was determined to be: 31.06% molasses, 0.73 g/L SDBS, 1.68% glycerol, and 1.50% CaCl2. Experimental validation confirmed the model’s reliability, showing < 3% deviation between predicted and actual performance metrics. Field evaluation produced significant results: small-scale testing with 2.5-ton and 4.4-ton mine vehicles maintained dust-free conditions for three consecutive days, while medium-scale trials with loaded (550-ton) and unloaded (225-ton) haul trucks achieved effective dust control for over 6 h. The suppressant creates a durable, homogeneous consolidation layer with substantial mechanical strength when applied. The suppression mechanism combines immediate dust wetting with prolonged suppression via dust particle solidification post water evaporates.